Electrophysiological Responses to Errors and Feedback in the Process of Action Regulation. - Luu, Phan; Tucker, Don M.; Derryberry, Douglas (Psychological Science., 2003)
A study was conducted study to gauge electrophysiological responses to mistakes and feedback in the process of action regulation. Data were drawn from analysis of participants performing a task in which evaluative feedback was delayed, so that it was irrelevant to immediate response control but kept its emotional value as a performance indicator. Findings revealed that a medial frontal feedback-related negativity similar to the error-related negativity (ERN) tracked affective response to the feedback and predicted subsequent performance. In addition, source analysis of the feedback-related negativity and ERN indicated a common dorsomedial anterior cingulate cortex (ACC) source and a rostromedial ACC source particular to the ERN. Moreover, that these sources are oscillatory in nature offers further proof that the ERN reflects ongoing theta activity generated in the mediofrontal regions.